Analysis of Household Energy Poverty on Human Development Outcomes in South Africa, Using the National Income Dynamics Survey (NIDS) - Gebers, Sophie (School of Economics, 2024)
Despite progress in post-Apartheid South Africa's electrification rates, especially in the country's rural areas, widespread energy poverty persists at the household level. To understand the dynamics of energy poverty at the micro-level, this dissertation examines how two different measures of energy poverty – namely, the Multidimensional Energy Poverty Index (MEPI) and the Ten-Percent Threshold measure (TPT) – affect human development outcomes in the domains of health, labour market outcomes and education-related outcomes. The MEPI is constructed using a range of dimensions relating to access to modern energy services captured in a nationally representative panel dataset, the National Income Dynamics Survey (NIDS). I also construct the TPT using variables pertaining to household energy expenditure and income. Although there were improvements from 2008 to 2017, it was found that multi- dimensional energy poverty is still prevalent in South African households, especially in rural and low-income households. The dissertation then turns to regression methods to establish whether there is an effect between energy poverty and human outcome indicators. I run both OLS and FE estimation strategies. However, empirical tests and prior literature points to the issue of potential endogeneity within the energy poverty variable. I utilize district-level electricity price and the percentage of households in the district using biomass as a fuel source as instrumental variables to correct for the endogeneity issue. Using a 2SLS regression model, the findings reflect that multidimensional energy poverty does indeed have adverse consequences for an adult individual's health outcomes – both subjective and objective measures. The results also point to the negative effect of household energy poverty on an individual's likelihood to participate in the labour force and be in employment. These results are all highly significant. Lastly, I establish that multidimensional energy poverty is associated with lower number of school years and higher likelihoods of missing a school day. I also show that energy poverty has a gendered effect, with women in the household often experiencing worse outcomes. The TPT is used in a sensitivity analysis. Overall, the results from the investigation can assist in advising policymakers on how access to modern, clean energy sources can help individuals' development outcomes in South Africa. Keywords: energy poverty, development outcomes, instrumental variable.